Фактори емоційного вигорання програмістів, що відрізняються ціннісним ставленням до професійної діяльності - Григоренко, Ю. В. (ХНУРЕ, 2020)
These theses disclose the problem of emotional burnout among programmers, who has a value attitude to their professional activity. Here are the possible factors that contribute to this phenomenon, including personal qualities, the features of interaction of the programmer with his professional environment and how can they influence each other. Also there are such mentioned and described concepts, as burnout syndrome, resistance and altruism with the properties that may enhance them. At the end of the research there are some contradictions, that were made up in order to reflect the main causes of the emotional burnout problem
Keywords: філософія; фактори емоційного вигорання